Peningkatan Kinerja UMKM Melalui Financial Technology dan Inklusi Keuangan Dengan Perilaku Keuangan Sebagai Mediasi - Yudie Fitrianto; Nuryasman Nuryasman; Faizul Mubarok (Dinasti Review, 2026)
This study aims to analyze the direct and indirect influence of financial technology and financial inclusion on MSME performance through the role of financial behavior as a mediating variable. The population used was all 1,511 MSMEs in Demak Regency. The sampling technique used purposive sampling, with the criteria being MSMEs in Demak Regency who had been operating for more than one year and had utilized fintech services to support their businesses. A total of 108 respondents were selected. The data analysis technique used was Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results showed that financial technology had a positive and significant effect on financial behavior, and financial inclusion had a positive and significant effect on financial behavior. The results also showed that financial technology had a positive and significant effect on MSME performance, financial inclusion had a positive and significant effect on MSME performance, and financial behavior had a positive and significant effect on MSME performance. The results of the mediation test showed that financial behavior can mediate the influence of financial technology and financial inclusion on MSME performance.